Bodiniosides S–Y, Seven New Triterpenoid Saponins from Elsholtzia bodinieri and Their Anti-Influenza Activities - Linyao Yang (MDPI AG, 2021)
Investigation of the n-BuOH extract of the aerial parts of Elsholtzia bodinieri led to the isolation of seven new triterpenoid saponins, Bodiniosides S–Y (1–7, resp.). Their strictures were elucidated on the basis of spectroscopic techniques, including HSQC, HSBC, and HSQC–TOCSY experiments, together with acid hydrolysis and GC analysis. The anti-influenza activities of compounds 1–7 were evaluated against A/WSN/33/2009 (H1N1) virus in MDCK cells. The results showed that compounds 2 and 5 exhibited moderate anti-influenza activities against A/WSN/33/2009 (H1N1), with inhibition rates of 35.33% and 24.08%, respectively.